Phase change material coat for battery thermal management with integrated rapid heating and cooling functions from −40 °C to 50 °C. (June 2021) - Luo, Mingyun; Song, Jiaqi; Ling, Ziye; Zhang, Zhengguo; Fang, Xiaoming
Abstract: This study reports an electric-conductive paraffin/expanded graphite (EG) composite phase change material (cPCM) for thermal management of lithium-ion battery in a harsh environment. In this cPCM, EG provides a support matrix for paraffin to prevent liquid leakage, as well as a network for thermal and electrical conduction. EG (20 wt%) gives the non-conductive paraffin with a low resistance 0.1–0.28 Ω mm, but also enhances its thermal conductivity by up to 960%. A numerical model has been developed and validated to reveal the mechanism of this full-temperature thermal management. This cPCM integrates heating and cooling together, thereby preheating batteries with Joule heat effect, and cooling down the battery with the thermal storage. At a voltage of 3.4 V, cPCM can heat an eight-cell module at 13.4 °C/min with a maximum temperature difference between cells, 3.3 °C. Meanwhile, the cPCM can also reduce the battery temperature from 77 °C to 43 °C during a high-rate discharge (3C). The battery temperature can be maintained within 20 °C–55 °C for the entire discharge process. This full-temperature thermal management can be extended to an enlarged battery pack consisting of seven modules, which provide a comfortable thermal environment of 20–55 °C for the batteries under extreme conditions of −40 +50 °C. This work broadens the application of PCM from a mere cooling function to a full-temperature thermal management. Graphical abstract: Image 1 Highlights: An electric-conductive composite phase chang material (cPCM) is applied to thermal management. The electrical and thermal conductivity of CPCM can be regulated by adjusting the density of EG. At a voltage of 3.4 V, the cPCM can heat an eight-cell battery module at 13.4 °C/min. The cPCM integrates heating and cooling and can widen the operating temperature of the battery to −40 °C ∼ +50 °C.